SPACE VECTOR ANALYSIS IN ELECTRICAL DRIVES FOR SINGLE-PHASE INDUCTION MOTOR USING MATLAB/SIMULINK - Anggun, Anugerah; Sulaiman , Marizan; Omar, Rosli (Little Lion Scientific Islamabad Pakistan, 2009)
Space Vector Pulse Width Modulation (SVPWM) has become the successful techniques to construct threephase sine wave Voltage Source Inverter (VSI) parallel to control three-phase motor using vector control. In this paper we present the analysis of SVPWM to construct two-phase sine wave VSI for single-phase induction motor. We also describes the modulation technique refer to dq components of main and auxiliary windings of single-phase induction motor. The VSI have four legs for this single-phase induction motor, and the four switching sequences had simulated in MATLAB and SIMULINK. The simulation result shows the feasibility of the proposed modulation techniques to drive single-phase induction motor.